“The True Kabbalah”: A Note on Martin Luther's Interpretation of Galatians 3:13 - Yeago, David S. 1956- (2022)
Luther's striking 1535 interpretation of Galatians 3:13 is not a theological effusion hung loosely on the text but a careful exegetical exercise in “Scripture interpreting Scripture” in which each key move is authorized by the pressure of other texts within the canon. For Luther, therefore, the “literal sense” of Galatians is not accessible apart from its entanglement in a canonical interpretive network. Further, the reality of which the text speaks is discovered only by entering into this complex intra-canonical web of hermeneutical interactions. Scripture's words therefore relate to theological reality not by extrinsic reference but quasi-sacramentally, following the pattern of Luther's theology of the means of grace.
Keywords: Redemption; person of Christ; justification by faith; sacramental hermeneutics; Canonical interpretation; hermeneutics theological interpretation; Galatians; Martin Luther